Anisotropic Strange Star Model Beyond Standard Maximum Mass Limit by Gravitational Decoupling in f(Q)$f(Q)$ Gravity. Issue 11 (30th September 2022) - Maurya, S. K.; Singh, Ksh. Newton; Lohakare, Santosh V.; Mishra, B.
Abstract: The current theoretical development identified as the gravitational decoupling via Complete Geometric Deformation (CGD) method that has been introduced to explore the nonmetricity Q effects in relativistic astrophysics. In the present work, we have investigated the gravitationally decoupled anisotropic solutions for the strange stars in the framework of f ( Q ) $f(Q)$ gravity by utilizing the CGD technique. To do this, we started with Tolman metric ansatz along with the MIT Bag model equation of state related to the hadronic matter. The solutions of the governing equations of motions are obtained by using two approaches, namely the mimicking of the θ sector to the seed radial pressure and energy density of the fluid model. The obtained models describe the self‐gravitating static, compact objects whose exterior solution can be given by the vacuum Schwarzschild Anti‐de Sitter spacetime. In particular, we modeled five stellar candidates, viz., LMC X‐4, PSR J1614‐2230, PSR J0740+6620, GW190814, and GW 170817 by using observational data. The rigorous viability tests of the solutions have been performed through regularity and stability conditions. We observed that the nonmetricity parameter and decoupling constant show a significant effect on stabilizing to ensure the physically realizable stellar models. The innovative feature of this work is to present the stable compact objects with masses beyond the 2 M ⊙ $2 M_{\odot }$ without engaging of exotic matter. Therefore, the present study shows a new perception and physical significance about the exploration of ultra‐compact astrophysical objects. Abstract : In the present work, the authors have investigated the gravitationally decoupled anisotropic solutions for strange star in the framework of f (Q) gravity by utilizing the CGD technique. To do this, they started with Tolman metric ansatz along with the MIT Bag model equation of state related to hadronic matter. The solutions of the governing equations of motions are obtained by using two approaches, namely the mimicking of the θ sector to the seed radial pressure and energy density of the fluid model. The obtained models describe the self‐gravitating static, compact objects whose exterior solution can be given by the vacuum Schwarzschild Anti‐de Sitter spacetime. In particularly, models are created for five stellar candidates, viz., LMC X‐4, PSR J1614‐2230, PSR J0740+6620, GW190814 and GW 170817 by using the observational data. The rigorous viability tests of the solutions have been performed through the regularity and stability conditions. One observes that the nonmetricity parameter and decoupling constant show the significant effect on stabilizing to ensure the physically realizable stellar models. The innovative feature of this work is to present the stable compact objects with the masses beyond the 2 M⊙ without engaging of exotic matter. Therefore, the present study shows a new perception and physical significance about the exploration of ultra‐compact astrophysical objects.